MERANCANG LEMBAGA KEUANGAN MIKRO SYARIAH YANG TEPAT PADA DESA CIBENING, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Thantawi, Tubagus Rifqy; Anwar, Miftakhul; Niswatin (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
Islamic banks and Islamic microfinance institutions (LKMS) are financial institutions that are oriented towards improving people's welfare, and microfinance is needed by small and medium-sized groups of people both for consumption and production as well as for business capital. Therefore a community service program is needed through outreach that can support economic growth in the region. This community service activity is carried out with the aim of providing knowledge and information to the public regarding how to choose the right financing product based on Islamic sharia through collaboration with sharia financial institutions. This community service was carried out in Cibening Village, Pamijahan District, Bogor Regency.